Some insights on the development of economic sciences through the lens of the Nobel Prize - Jajuga, Krzysztof (Publishing House of Wroclaw University of Economics and Business, 2025)
The paper discusses the key developments in the area of economic sciences. The insights are derived from the analysis of the achievements of the laureates of the prize in economic sciences in memory of Alfred Nobel.
Argumenta Oeconomica, 2025, Nr 2 (55), s. I-VIII
Keywords: economic sciences; technology; economic growth; Nobel Prize